Learned fear extinction: an interdisciplinary investigation of the neurocircuitry and the potential therapeutic benefit of cannabidiol - Jurkus, Regimantas (2019)
Fear memory and extinction are psychological processes believed to be dysfunctional in several anxiety disorders. We studied these processes using pharmacological, computational modelling and electrophysiological approaches to understand their neurochemical modulation as well as mediation by several brain areas. First of all, considering the well documented anxiolytic effect of the phytocannabinoid cannabidiol (CBD) in contextual fear memory and innate fear paradigms, we investigated its effects in auditory fear memory and extinction in rats. Our experiment revealed that CBD reduced auditory fear memory expression without impairing extinction. CBD also reduced contextual fear prior to extinction, consistent with previous findings. Our results indicate that CBD reduces learned fear associated with explicit cues, and support the potential use of CBD together with psychological treatments of anxiety disorders in the future.